Diagnostic labels of NANDA-I in a southern region of Spain - Rafael González-Rodríguez; María de los Ángeles Martelo-Baro; Pilar Bas-Sarmiento
ABSTRACT Objective: to determine the incidence of NANDA-I diagnostic labels (North American Nursing Diagnosis Association-International) and to establish the distribution of cases of assistance and the associated labels, according to sociodemographic variables (age and sex). Method: descriptive, cross-sectional epidemiological study of labels of NANDA-I, under ecological design. The distribution of labels was analyzed according to sex and age; the corresponding frequencies were calculated and for each label the incidence were calculated rates with aggregate data from the attended cases. Results: the total number of cases of care under study was 9,928 (41.65% men and 58.35% women). The identified labels were 16,456 (7,084 men and 9,372 women); average of 1.7 labels per case of care; Out of 216 labels proposed by NANDA-I, in its 2012-14 classification, 152 were used, representing 70.4%. The labels with the highest incidence rates per thousand inhabitants were: Anxiety, Willingness to Improve Knowledge and Risk of Infection. Conclusions: the study allowed detecting, through NANDA-I, the answers to the health problems of greater incidence in the users attended.